Lethal decisions : the unnecessary deaths of millions of women and children from HIV/AIDS - Ammann, Arthur J., 1936- (Vanderbilt University Press, 2016)
"This book chronicles the discovery of AIDS in a handful of infants beginning in 1981 and the remarkable scientific progress in prevention and treatment over the 15 years that followed"--Provided by publisher.